Ocean grabbing and gender-based resistance: A literature review with a Feminist Political Ecology (FPE) - Albar, Ardianingtyas Ibni; Siscawati, Mia (Program Pascasarjana Universitas Negeri Yogyakarta, 2025)
The seizure of coastal areas by the state and private capital through large-scale development projects has created a complex social and ecological crisis. This article reviews the literature on coastal agrarian conflicts, focusing on power relations, gender dynamics, community resistance strategies, and the impact of ocean grabbing on social structures and communal bonds. Research consistently shows that these projects reshape physical landscapes, trigger agrarian conflicts, and displace local communities, thereby commodifying living spaces. Women, often the most vulnerable group, play strategic roles as guardians of community values, actors in alternative economies, and symbols of living spaces. While local communities resist through mobilization, legal channels, and advocacy, complex power relations often obscure women’s contributions in narratives of resistance. This dispossession also fractures community solidarity through tactics of divide-and-rule and repression. Employing a Feminist Political Ecology (FPE) framework, this article emphasizes the importance of gender-based and intersectional approaches in understanding coastal agrarian conflicts. Future research should therefore pay greater attention to women’s strategies in defending their living spaces through their lived experiences and gender identities, employing feminist perspectives to advance more comprehensive gender justice.